2020
DOI: 10.3390/diseases8010007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress and Cardiovascular Disease among Individuals Exposed to Lead: A Pilot Study

Abstract: Chronic stress and cardiovascular disease risk were explored in a predominately middle-aged adult population exposed to elevated lead levels in this cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) from the period 2007-2010. Elevated lead exposure was defined using the epidemiological threshold of a blood lead level (BLL) > 5 μg/dL as defined by the U.S. Centers for Disease Control and Prevention (CDC). Allostatic load (AL), a measure of chronic stress, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Each individual in the study was assigned a value of 1 if they are in the high-risk category or a 0 if in the low-risk category for all markers to calculate a total AL value out of 10. Clinical and laboratory collection and analysis of markers and variables of interest have been described elsewhere [ 35 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each individual in the study was assigned a value of 1 if they are in the high-risk category or a 0 if in the low-risk category for all markers to calculate a total AL value out of 10. Clinical and laboratory collection and analysis of markers and variables of interest have been described elsewhere [ 35 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Technical details of the survey, including sampling design, data collection protocols, and data availability, are freely available on their website. Data collection for NHANES makers of interest have been described elsewhere [ 35 ]. This study used de-identified secondary data; hence, the study did not require IRB approval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to distress can come from several sources such as occupation, family life, emotional problems, and can alter the health of various populations [ 38 , 39 , 40 ]. When combined with the exposure to lead via water, air, soil, dust, and food [ 41 , 42 , 43 ], the damage to the health of populations may suffer a combined or synergistic effect [ 16 , 26 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior studies [ 25 , 26 ], AL was operationalized via a cumulative index of dysfunction across multiple physiological systems such as the cardiovascular system (Systolic Blood Pressure—SBP, Diastolic Blood pressure—DBP, triglycerides, High Density Lipoprotein—HDL cholesterol, total cholesterol); the inflammatory system (C-reactive Protein—CRP for systemic inflammation); and finally the metabolic system (Albumin, Body Mass Index—BMI, hemoglobin A1C, and Creatinine Clearance). These markers were divided into quartiles based on their distribution within the database with high-risk for each biomarker considered the top quarter in the distribution for all markers apart from the markers for albumin, creatinine clearance, and for HDL cholesterol, for which the lowest quarter of the distribution was the highest risk [ 8 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%